Temperature induces metabolic reprogramming in fish during bacterial infection - Sun, Bin; Sun, Boguang; Zhang, Beibei; Sun, Li (Frontiers in Immunology, 2022)
Water temperature elevation as a consequence of global warming results in increased incidence of bacterial disease, such as edwardsiellosis, in fish farming. Edwardsiellosis is caused by the bacterial pathogen Edwardsiella tarda and affects many farmed fish including flounder (Paralichthys olivaceus). Currently, the effect of temperature on the metabolic response of flounder to E. tarda infection is unclear. In this study, we found that compared to low temperature (15°C), high temperature (23°C) enhanced E. tarda dissemination in flounder tissues. To examine the impact of temperature on the metabolism of flounder induced by E. tarda, comparative metabolomics were performed, which identified a large number of metabolites responsive to E. tarda invasion and temperature alteration. During E. tarda infection, the metabolic profile induced by elevated temperature was mainly featured by extensively decreased amino acids and TCA intermediates such as succinate, a proven immune regulator. Further, 38 potential metabolite markers of temperature effect (MMTE) in association with bacterial infection were identified. When used as exogenous supplements, two of the MMTE, i.e., L-methionine and UDP-glucose, effectively upregulated the expression of pro-inflammatory cytokines and suppressed E. tarda infection in flounder leukocytes. Taken together, the results of this study indicate an important influence of temperature on the metabolism of flounder during bacterial infection, which eventually affects the survivability of the fish. These findings underscore the risk of exacerbating disease induced by rising temperature in the context of global warming.